Semantic Graphs Derived From Triplets pplicwith Aation in Document Summarization - Rusu, D.; Fortuna, B.; Grobelnik, M.; Mladenić, D. (Informatica)
Semantic Graphs Derived From Triplets pplicwith Aation in Document Summarization